Rhenium(i) terpyridine complexes – synthesis, photophysical properties and application in organic light emitting devices. Issue 4 (24th December 2015) - Klemens, Tomasz; Świtlicka-Olszewska, Anna; Machura, Barbara; Grucela, Marzena; Schab-Balcerzak, Ewa; Smolarek, Karolina; Mackowski, Sebastian; Szlapa, Agata; Kula, Slawomir; Krompiec, Stanisław; Lodowski, Piotr; Chrobok, Anna
Abstract : The structural and photophysical characterization of new Re(i ) complexes was reported. Abstract : Six new Re(i ) complexes of the general formula [ReCl(CO)3 (4′-R-terpy-κ 2 N)] with 2, 2′:6′, 2′′-terpyridine-based ligands have been synthesized and characterized by IR, NMR ( 1 H and 13 C), UV-Vis spectroscopy and single crystal X-ray analysis. The luminescent properties of [ReCl(CO)3 (4′-R-terpy-κ 2 N)] were studied in solution and solid state, at 298 and 77 K, respectively. To obtain detailed insight into the electronic structures and spectroscopic properties of [ReCl(CO)3 (4′-R-terpy-κ 2 N)], the density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were performed. Also, the suitability of this class of materials for being applied in organic light emitting diodes (OLEDs) has been preliminarily tested.